استخدام منهجية Box-Jenkins للتنبؤ ببعض مؤشرات سوق الأسهم السعودي خلال الفترة من جانفي 2010م إلى غاية ديسمبر 2017م - عتروس, سهيلة; عتروس, صبرينة (Recherches économiques et managériales, 2020)
تهدف هذه الدراسة إلى تسليط الضوء على عملية التنبؤ وأساليبه وإبراز أهميته في معرفة القيم المستقبلية بهدف ترشيد القرارات ورسم الاستراتيجيات، وكذا تقريب وتوضيح المفاهيم الخاصة بمنهجية Box-Jenkins باعتبارها أسلوب حديث وفعال في تحليل السلاسل الزمنية والتنبؤ. فمن خلال تطبيق المراحل المختلفة لمنهجية Box-Jenkins على السلسلة الزمنية الشهرية لكل من مؤشر القيمة السوقية للأسهم ومؤشر عدد الأسهم المتداولة في سوق الأسهم السعودي سمحت بالحصول على نموذج قياسي فعال للتنبؤ بالقيم المستقبلية لكلا المؤشرين يسمح بإعطاء نتائج قريبة من الواقع. الكلمات المفتاحية: التنبؤ، منهجية Box-Jenkins ، سوق الأسهم السعودي، مؤشرات سوق الأسهم السعودي. Abstract : This study aims to shed light on the process of prediction and its methods and highlight its importance in knowledge of future values in order to rationalize decisions and draw strategies, as well as to bring and clarify the concepts of the methodology of Box-Jenkins as a modern and effective method in time series analysis and prediction. By applying the different phases of the Box-Jenkins methodology to the monthly series of the Market Capitalization and Number of Shares Traded on the Saudi share market, it has been possible to obtain an effective standard model to predict the future values of both indicators. Abstract : prediction, methodology of Box-Jenkins,  Saudi share market, Saudi share market indicators